Proyecto de factibilidad para la implementación de un autoservicio, en la ciudad de Macará de la provincia de Loja, en el año 2016 - Tacury Torrez, Karla Fernanda (2017)
The self - service market implementation in the Macará district is developing in order to satisfy and save the objective needs in to the hold homes around the district, information has been researched told us how productive and important this project will be. The corporate name that was determinate in this project is “Autoservicio EL AHORRO EURL”, name with in a useful business cycle of 5 years, addressed in a downtown sector of Macará district and city. Located on street Manuel Enrique Rengel and Sebastian Valdivieso The research methodology is shared in four official stamens into this Thesis Project where we can find the hold techniques and a tool used in order to get the valuable information has done. The market study was carried out based on a survey applied to the families of the city of Macará; Subsequently proceeded to determine the potential demand 4870 families, real demand 2289 families; Effective demand represents 89% ie 2037 families, the average consumption per annual family was realized and an unsatisfied demand of $ 279851.66 was obtained The balance sheet established all investment by deferred and current fixed assets that have been rose to $ 42000.43 dollars going to be financed by itself in a 52.38% and the 47.62% by external economics sources from BNF loan as recover as amortized in an installment of 8 pays in a term of 4 years. The sings of financial feasibility yield positives and encouraging results in order to increase this project does giving a flow cash of 40092.44 by the first year within a lost and gain it does obtain for a net utility of 33304.81; the actual net cost is posivity rise than 136911.40. The internal rate of return (IRR) being in a 93.57% over the capital cost, being available do any action of invest in this Project. The relation of benefit/cost gives a statement of 1.21 dollars representing the useful productivity from this project, In the other hand in each dollar inverted the result will be 0,21 dollars of benefit, affording within 3 years, 11 months, 8 days as a period of recovery. Besides, it shows an increase of 14.74% in the services costs and products and 11.75% of income decrease, giving a major ratability this project. However as far as state in question about company organization I share that these companies had the status of one person limited liability undertakings (EURLs), the General Meeting of Shareholders, Management, Standards and legal affairs, General Secretary, Baggage, Accounting Department and Sales Department.